Neoadjuvant immunotherapy and neoadjuvant chemotherapy in resectable non-small cell lung cancer: A systematic review and single-arm meta-analysis - Wang, He; Liu, Tingting; Chen, Jun; Dang, Jun (Frontiers in Oncology, 2022)
Background It remains uncertain whether neoadjuvant immune checkpoint inhibitor (nICI) is superior to neoadjuvant chemotherapy (nCT) in resectable non-small cell lung cancer. In addition, there are outstanding questions for nICI such as the ideal treatment mode and predictors. Methods PubMed, Embase, Cochrane Library, Web of Science, and scientific meetings were searched for eligible single-arm or multi-arm trials until 31 December 2021. The primary outcomes of interest were major pathological response (MPR) and pathological complete response (pCR). The random-effect model was used for statistical analysis. Results Twenty-four trials of nICI (n = 1,043) and 29 trials of nCT (n = 2,337) were identified. nICI combination therapy was associated with higher MPR (63.2%, 95% CI: 54.2%–72.1%) and pCR (35.3%, 95% CI: 27.4%–43.3%) rates compared to nCT (16.2%, 95% CI: 7.5%–25.0%, P < 0.001 and 5.5%, 95% CI: 3.5%–7.5%, P < 0.001) and nICI monotherapy (23.3%, 95% CI: 12.7%–33.8%, P < 0.001, and 6.5%, 95% CI: 1.7%–11.2%, P < 0.001). As for safety, nICI monotherapy had the best tolerability; nICI combination showed a similar surgical resection rate and higher R0 resection rate compared to nCT. PD-1 inhibitor and high PD-L1 expression (≥1% or ≥50%) were correlated with higher MPR and pCR rates compared to PD-L1 inhibitor and PD-L1 expression <1%. Conclusions nICI combination therapy is associated with higher MPR and pCR rates compared to nCT and nICI monotherapy. PD-1 inhibitor seems to be superior to PD-L1 inhibitor. PD-L1 status appears to be predictive of MPR and pCR for patients receiving nICI. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=278661, CRD42021278661.